Between Rules and Discretion: Thoughts on Ordo-liberalism - Jonathan White (London School of Economics and Political Science (LSE), European Institute, 2017)
The paper examines how efforts to design a policy regime governed by rules may lead on the contrary to recurrent and far-reaching political discretion. Where re-orientations of policy are formally excluded, as in the ordo-liberal perspective, unforeseen situations will typically provoke last-minute unconventional actions, whether in the form of temporary exceptions to the existing framework or moves to constitute a new one. In order to preserve the ideal of a rule-governed order, such actions must be cast as extraordinary measures for exceptional times – as the politics of emergency, that is. Whereas modern political thought of various stripes tends to defend constitutional rules as the condition of policy discretion, here one sees the converse scenario of constitutional discretion pursued in the name of policy rules. These themes are elaborated in connection with the ongoing crisis of the European Union.
Keywords: 330; Ordo-liberalism; Germany; Euro Crisis; European Union